Ultrasound-guided fine needle aspiration cytology of Para-aortic lymph node metastasis in uterine cervical cancer: diagnostic accuracy and impact on clinical decision making - Junping Liu (BMC Cancer, 2021)
Abstract Objective The main aim of this study was to ascertain the effectiveness of ultrasound-guided fine needle aspiration cytology (US-FNAC) in the diagnosis of para-aortic lymph node (PALN) metastasis in uterine cervical cancer and to establish its potential impact on clinical therapeutic decision making. Methods We retrospectively reviewed clinical data from 92 patients diagnosed with cervical cancer with PALN enlargement between 2010 and 2018. Cytological results obtained with US-FNAC were classified by the same experienced cellular pathologists. Diagnostic indicators were determined on the basis of biopsy, imaging and clinical follow-up results. Univariate and multivariate analyses were used to assess the differences of influencing factors. The effect of US-FNAC on clinical decision making was evaluated. Results Cytological results of US-FNAC were categorized as malignancy (n = 62; 67.4%), suspicious malignancy (n = 11; 12.0%), undetermined (n = 5; 5.4%), benign (n = 10; 10.9%), and inadequate (n = 4; 4.3%). Satisfactory biopsy samples were obtained from 95.7% of PALNs sampled (88/92). The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of FNAC in distinguishing benign from malignant cases were 90.1% (95% CI: 0.809–0.953), 100% (95% CI: 0.561–1), 100% (95% CI: 0.938–1), 46.7% (95% CI: 0.223–0.726) and 90.9% (95% CI: 0.848–0.970), respectively. Univariate analysis indicated significant differences in experience of puncture physicians (radiologists) between the correct and wrong diagnosis groups (P < 0.05), which was further confirmed as an independent predictor of diagnostic accuracy in multivariate analysis (p = 0.031, OR = 0.077, 95% CI: 0.354–0.919). All patients tolerated the US-FNAC procedure well and only nine presented slight abdominal discomfort. The therapeutic strategies for 74 patients (80.4%) were influenced by US-FNAC findings. Conclusions US-FNAC was a relatively safe and effective technique for examination of enlarged para-aortic lymph nodes and may therefore serve as a routine diagnostic tool to guide clinical decision making for management of cervical cancer.